Corporate Control and the Financial System in Germany: Recent Changes in the Role of Banks - Ettore Andreani (Universität Rostock, Institut für Volkswirtschaftslehre, 2003)
The present paper aims to analyze the major changes in the German system of cross-holdings between banks and industrial or financial companies. After an overview on the role of banks in bank-based versus market-based financial systems, and on the German system of corporate control, we focus our attention on the relationship not only between banks and industrial companies, but also between financial companies in Germany. Discussing the reasons for cross-holdings within the financial sector, we hypothesize that cross-holdings are less efficient than full mergers. We analyze hypotheses about the structure of the Deutschland AG and about a different role of cross-holdings at different levels of the German financial system. A test of hypotheses on recent mergers and acquisitions in the German financial system yields that they explain some of the changes in the cross-holdings occurred after 1994. We conclude that instead of the often referred Macht der Banken the German financial system is characterized by an increasing importance of insurance companies.
Keywords: 330; Corporate Governance; Finanzsektor; Bank; Versicherung; Unternehmenskonzentration; Deutschland